2022
DOI: 10.2478/aoj-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of 2D and 3D cephalometry: a systematic review and meta-analysis

Abstract: Objectives To compare the measurement of cephalometric parameters using 3D images obtained from CBCT to 2D images obtained from a conventional cephalogram. Methods An electronic literature search was conducted using PubMed, Embase, Web of Science, CNKI, CENTRAL, and the grey literature database of SIGLE (up to May 2021). The selection of the eligible studies, data extraction, and an evaluation for possible risk of bias (Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a recent systematic review, it was concluded that cephalometric analyses using CBCT-scans have similar levels of accuracy to cephalometric analyses using conventional 2D cephalograms. CBCT was only recommended when the conditions required more-advanced diagnostics for treatment planning [ 34 ]. The higher radiation dose from CBCT explains why conventional cephalometry remains the preferred option in many countries, since justification and optimisation of radiographic examinations are required; these include keeping the radiation dosages as low as diagnostically acceptable, especially for young patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, it was concluded that cephalometric analyses using CBCT-scans have similar levels of accuracy to cephalometric analyses using conventional 2D cephalograms. CBCT was only recommended when the conditions required more-advanced diagnostics for treatment planning [ 34 ]. The higher radiation dose from CBCT explains why conventional cephalometry remains the preferred option in many countries, since justification and optimisation of radiographic examinations are required; these include keeping the radiation dosages as low as diagnostically acceptable, especially for young patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%